Tunable optical properties of push-pull chromophores: End group effect. Issue 32 (6th August 2020) - Tonga, Murat
Graphical abstract: Highlights: A-π-D-π-A type chromophores with various acceptor groups were synthesized. The effects of end group tuning on optical and electronic properties were studied. The use of ICT yielded strong absorption throughout the visible region (1.8–2.2 eV). They gave excellent molar extinction coefficients (45, 000–101, 500 M −1  cm −1 ). DFT calculations compare the correlation between structures and optical properties. Abstract: A series of A-π-D-π-A type symmetrical push-pull chromophores with various end groups ( e.g., trifluoroacetone, indanone, dicyano, isoxazolone and pyrazolinone) linked through a symmetric π- conjugated backbone (EDOT-phenylene vinylene-EDOT) was synthesized. The effect of end group tuning on optical properties was intensively investigated by UV–visible absorption, fluorescence spectroscopy and DFT calculations. A broad range of chromophores showing strong absorption was achieved with a fine alteration of the electron-accepting strength of the terminal acceptors. The optical investigation demonstrated that their low optical band gap (1.8–2.2 eV) combined with outstanding molar absorptivity (45, 000–101, 500 M −1  cm −1 ) which would provide strong light-capturing capability.